Air pollution: the emergence of a major global health risk factor. Issue 6 (15th October 2019) - Boogaard, Hanna; Walker, Katherine; Cohen, Aaron J
Abstract: Air pollution is now recognized by governments, international institutions and civil society as a major global public health risk factor. This is the result of the remarkable growth of scientific knowledge enabled by advances in epidemiology and exposure assessment. There is now a broad scientific consensus that exposure to air pollution increases mortality and morbidity from cardiovascular and respiratory disease and lung cancer and shortens life expectancy. Although air pollution has markedly declined in high-income countries, it was still responsible for some 4.9 million deaths in 2017, largely in low- and middle-income countries, where air pollution has increased over the past 25 y. As governments act to reduce air pollution there is a continuing need for research to strengthen the evidence on disease risk at very low and very high levels of air pollution, identify the air pollution sources most responsible for disease burden and assess the public health effectiveness of actions taken to improve air quality.